2022
DOI: 10.1007/s42757-021-0125-3
|View full text |Cite
|
Sign up to set email alerts
|

Towards the efficient modelling of trapped air pockets during squeeze flow

Abstract: In most bonding processes, an adhesive is applied to a substrate in a specific pattern before the second substrate is subsequently pressed against it. During this, the adhesive flows in such a way that, ideally, it completely fills the joint. In practice, however, areas with entrapped air frequently remain in the bonded adhesive layer. Within the scope of a research project, these flows are systematically analyzed in order to identify optimal initial application patterns for the adhesive and substrate geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The original PFGM, with closing gaps, has already been successfully validated for various complicated cases in the forward simulation (Kaufmann et al, 2022;Kaufmann et al, 2023a;Müller et al, 2018;Müller et al, 2023;Müller et al, 2022). Thus, the forward simulation offers a good possibility to validate the adapted reverse-model in the focus of this paper.…”
Section: Validationmentioning
confidence: 97%
See 1 more Smart Citation
“…The original PFGM, with closing gaps, has already been successfully validated for various complicated cases in the forward simulation (Kaufmann et al, 2022;Kaufmann et al, 2023a;Müller et al, 2018;Müller et al, 2023;Müller et al, 2022). Thus, the forward simulation offers a good possibility to validate the adapted reverse-model in the focus of this paper.…”
Section: Validationmentioning
confidence: 97%
“…In recent years, it has been extended, and experimentally validated (Kaufmann et al, 2022;Kaufmann et al, 2023a), to simulate adhesive flows (Müller et al, 2018). Further extensions allowed the inclusion of air bubbles (Müller et al, 2023) and the behaviour of non-Newtonian fluids, which most adhesives are (Müller et al, 2022). The PFGM is a very efficient method for numerically modelling adhesive flow in narrow gaps.…”
Section: Simulation Tool Pfgmmentioning
confidence: 99%
“…Stable water-in-oil (W/O) emulsions are readily formed during crude oil production due to the wide application of polymer flooding, surfactant flooding, and alkali flooding. Electrostatic separation is adopted widely in oil–water separation, which becomes one of the most common technologies in petroleum extraction because of its advantages of being efficient, controllable, and environmentally friendly. Experimental research has found that electromagnetic synergy has a higher efficiency in enhancing oil–water separation than a single electric field. EMSF alters the behavior of natural salt ions in crude oil, which would affect the coalescence process of droplets. However, there is a lack of detailed research on the electrocoalescence behavior of droplets dispersed with salt ions under EMSF.…”
Section: Introductionmentioning
confidence: 99%
“…This mathematical transformation makes it analogous to a lifting Hele-Shaw cell process [5]. For this task, the Partially Filled Gap Model (PFGM) [3,[6][7][8][9] was used. It very efficiently models fluid flow in narrow gaps.…”
Section: Introductionmentioning
confidence: 99%